Microclimatic conditions and seed cotton yield as affected by sowing time, row orientation and plant spacing under Bt cotton hybrid - ABHISHEK , DHIR; R K, PAL; P K, KINGRA; S K, MISHRA (MAUSAM, 2020)
Microclimatic modifications are the effective and suitable adaptation strategy to minimize the adverse affect of weather on cotton. In this context, multi-location field experiments were laid out at Bathinda and Faridkot, districts of Punjab during Kharif 2018 with Bt-cotton hybrid RCH 773 BGII and sown at three times i.e., April 30, May 15 and May 30 with two row orientations (North-South: N-S and East-West : E-W) and three plant spacing’s (67.5 cm × 45.0 cm, 67.5 cm × 60.0 cm and 67.5 cm × 75.0 cm) in factorial split plot design and replicated by three times. The results revealed that during the morning (0730 IST) and afternoon time (1430 IST), soil and within-canopy temperature were found higher during emergence and mid growth stages with delayed sowing which reduced the crop growing period and resulted the seed cotton yield to be declined with delayed sowing. On the other hand, morning and afternoon within-canopy relative humidity was recorded higher with delayed sowing during sensitive stages of the crop which provided favorable weather for higher infestation of cotton insect-pest and disease and caused reduction in seed cotton yield at both the study locations. Soil temperature and within-canopy temperature were recorded higher in East-West row oriented, while within-canopy RH was higher under North-South row orientation at both the study regions. During entire growth period of cotton, soil temperature and within-canopy temperature recorded during morning and afternoon hours were found to be increased with increase in plant spacing whereas within-canopy relative humidity during morning and afternoon hours was found to be decreased with increase in plant spacing at both the locations. Among microclimatic parameters, higher variation was observed between sowing dates, while lesser variation was recorded among row orientations and plant spacings.